Sleep duration impact on sleep quality, mood, and fitness in elite athletes with a natural menstrual cycle or hormonal contraceptive use - Baber, F.; Chassard, T.; Badier, N.; Lafitte, A.; Dupuit, M.; Saulière, G.; Debaud, E.; Toussaint, J.-F.; Antero, J. (Chronobiology International, 2025)
Little is known about the relationship between sleep quality and quantity associated with mood, fitness, and menstrual cycle status in elite athletes. This longitudinal prospective cohort study explores these relationships in a French cohort of elite athletes in preparation for the Olympic Games. Self-reported sleep patterns, quality, mood, fitness and menstrual cycles were monitored daily via smartphone applications from February 2021 to February 2024, involving 108 athletes and 13 852 observations. Generalized Estimating Equations were used to evaluate associations between these variables across three menstrual cycle status groups (i.e regular, irregular, or under hormonal contraception). Sleep duration significantly correlated with self-reported sleep quality (ß = 0.179), fitness (ß = 0.241), and mood (ß = 0.097) across all menstrual cycle status groups. Sleeping less than 8 h led to below-average scores in these parameters. Late bedtimes, especially after 11 PM for athletes with irregular cycles and after midnight for all groups, negatively impacted sleep quality, fitness, and mood. Athletes using hormonal contraception reported slightly longer sleep durations than those with regular (p < 0.04) or irregular cycles (p < 0.02). Despite individual variations, the cohort`s average sleep duration (8.5 ± 1.2 h) aligned with recommended guidelines. Sleep patterns significantly influence mood and fitness similarly among elite athletes with a regular or irregular menstrual cycle or under hormonal contraception. Further studies are needed to clarify the role of hormonal status in sleep and its long-term implications for athlete health.